3(4x+4)=-2(-2x+2)

Simple and best practice solution for 3(4x+4)=-2(-2x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+4)=-2(-2x+2) equation:


Simplifying
3(4x + 4) = -2(-2x + 2)

Reorder the terms:
3(4 + 4x) = -2(-2x + 2)
(4 * 3 + 4x * 3) = -2(-2x + 2)
(12 + 12x) = -2(-2x + 2)

Reorder the terms:
12 + 12x = -2(2 + -2x)
12 + 12x = (2 * -2 + -2x * -2)
12 + 12x = (-4 + 4x)

Solving
12 + 12x = -4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
12 + 12x + -4x = -4 + 4x + -4x

Combine like terms: 12x + -4x = 8x
12 + 8x = -4 + 4x + -4x

Combine like terms: 4x + -4x = 0
12 + 8x = -4 + 0
12 + 8x = -4

Add '-12' to each side of the equation.
12 + -12 + 8x = -4 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = -4 + -12
8x = -4 + -12

Combine like terms: -4 + -12 = -16
8x = -16

Divide each side by '8'.
x = -2

Simplifying
x = -2

See similar equations:

| 5-(2x-7)=10 | | (3)(2)(4)-(5)(2)(3)= | | x^2+x=2208 | | X+3y-5z=1 | | 3x-4+7x-20=6-5x+15-8x+6 | | ax(K-x)=0 | | x^2-10x-57=0 | | 4x^2+33x=-52 | | 19(v+1)-3v=4(4v+4)-18 | | X=42-3x-4x | | (4)1+2-1= | | -6n-6=30 | | -7x+6(8x+5)=-134 | | 2n+2n=4n | | 5x+6=12+9x-5 | | x-(16/100)x=17.64 | | 4w-26=28 | | 26=3(k-3) | | 6.5a-5.8=10.45 | | 4.2a+2.69=-11.17 | | -3-0.4x+4-0.3x= | | 6x-9y-4+2y= | | -8(5-x)=-88 | | 2x+24=4x-3 | | 5(y+2)=12 | | 11(-6)-y=-11 | | Sexy=3 | | 4y+2=y+11 | | p-1=5p+3p-9 | | 4z+3=6z-5 | | 9.7y+7.53=-54.55 | | 37x-15+44x-29=180 |

Equations solver categories